Effects of different sources of forage in high-concentrate diets on fermentation parameters, ruminal biohydrogenation and microbiota in Nellore feedlot steers - Messana, J. D. [UNESP]; Carvalho, A. L.E.G.F. [UNESP]; Ribeiro, A. F. [UNESP]; Fiorentini, G. [UNESP]; Castagnino, P. S. [UNESP]; Granja-Salcedo, Y. T. [UNESP]; Pires, A. V.; Berchielli, T. T. [UNESP] (Cambridge University Press (CUP), 2016)
Modifying the extent of fatty acid (FA) biohydrogenation (BH) in the rumen through diet formulation is an effective strategy for changing the content of unsaturated FAs (USFAs) in meat. The present study investigated the effects of different sources of forage in high-concentrate diets on intake, digestibility, rumen fermentation, ruminal BH, duodenal flow of FAs and rumen microbiota in Nellore steers. Intake of neutral detergent fibre (NDF) was higher in animals fed with maize silage (MS) than in those fed with sugar cane (SC) and sugar cane bagasse (SB). Higher digestibility of dry matter and NDF was found in animals fed with MS than in those fed with the other diets. In addition, higher crude protein digestibility was observed in animals fed with sugar cane bagasse than in those fed with SC. Non-fibre carbohydrate (NFC) digestibility was higher in animals fed with sugar cane than in those fed with the other diets. Intake of total and individual FAs such as C18 : 1 cis-9, C18 : 2, and C18 : 3 was similar between animals fed with MS and SB, but decreased in animals fed with SC. Diets containing MS and SB showed higher total digestibility of saturated FAs (SFAs) and USFAs, respectively and total FAs and ruminal BH of C18 : 1 and USFA. Intestinal digestibility of overall FAs did not differ among treatments, except for C18 : 3, which increased in animals fed with SC and SB. The profile of FAs in duodenal digesta and faecal outputs did not differ among treatments. However, the flow of NDF was higher in animals fed with SC than in those fed with MS and SB. Animals fed with SB showed higher values of pH than those fed with MS and SC. Animals fed with SC showed lower values of ammonia-nitrogen. Protozoan counts were only influenced by diet for species that belonged to the genera Dasytricha and Isotricha. Populations of fibrolytic bacteria (Ruminococus flavefaciens, Ruminococus albus and Fibrobacter succinogenes) were similar among diets. Populations of Selenomonas ruminantium increased 2·5 and 5 times in animals fed with MS when compared with those fed with SC and SB, respectively. The use of MS increased intake and digestibility of NDF, and the use of SC decreased ruminal BH of total USFA without changing the flow of FAs to the duodenum. Thus, different sources of forage in high-concentrate diets do not modify the duodenal flow of USFA or fibrolytic bacteria. This must be taken into account when formulating diets to modulate ruminal upsets without altering intake.